4x-6y=12---->-6y=-4x+12--->y=(2/3)x-2posted by Alex Constancio
Reduce the equation to the standard form:
The constant term -2 is the y-intercept.
A x-intercept is a point on the graph where y is zero.
4 x - 6 y = 12
for y = 0
4 x - 0 = 12
4 x = 12 Divide both sides with 4
x = 3
x-intercept = 3posted by Bosnian
Oops, the question requires the x-intercept, which is in fact the root of the equation, so solve the equation by putting y=0 to get
(2/3)x=2, or x=3.
So the x-intercept is 3.
Also, the y-intercept can also be obtained by putting x=0 in the equation to get y=12/(-6)=-2.